Changes in Chinese Culture as Examined Through Changes in Personal Pronoun Usage - Hamamura, Takeshi; Xu, Y. (SAGE Publications Inc., 2015)
For the last several decades, Chinese society has experienced transformative changes in its social ecology. Is Chinese culture more individualistic today as a result? The current research examined this question by cross-temporally examining the usage of Chinese personal pronouns associated with individualism–collectivism. A Chinese corpus encompassing the period from 1950 to 2008 was analyzed using the Google Ngram Viewer. Cross-temporal changes in the usages of personal pronouns conceptually associated with individualism–collectivism were non-linear and highly similar to the patterns found for pronouns and non-pronoun words unassociated with individualism–collectivism. Follow-up analyses that disentangled these patterns indicated an increasing usage of individualistic pronouns and a decreasing usage of collectivistic pronouns in recent decades.